Treasury Information Management (TRIM) - V S Raghunathan A Nisarudeen
TRIM is designed and developed as a centralised repository of treasury transactions and related data to provide (government-to-government) G2G and government-to-citizen) G2C services. Payment and receipt transactions taking place in all the treasuries are brought to the Data Centre at the Directorate of Treasuries through the TIS (Treasury Information System) application on a daily basis through a dial-up network. Apart from maintaining individual transactions, the TRIM system upholds treasury-wise, date-wise, head-of-account-wise summary details for effective and fast information delivery. e-Government and citizen services are provided through the treasury portal http://treasury.kerala.gov.in.